Features of joint activity of students and teachers - Glukhov, Gennady Vasilyevich; Gromova, Tatiana Vladimirovna (Archives of Business Research, 2017)
Extensive use of distance education which is equivalent to traditional forms of education, implementing information and communication technologies are recognized as one of the priority tasks of education. Distance education in different forms contributes to the creation of a unified educational space, ensuring the possibility of obtaining standardized education to any person at any point in the educational space, regardless of his/her location, social and material status, physical condition, etc. Of great importance in the development and implementation of distance learning (DL) in educational institutions of various levels is the availability of teachers able and willing to carry out activities in the DL system. Characteristics, models and features of joint activities of teachers and students in the DL system, models of distance education as well as means and forms of DL are the subject of study in this article. The obtained results can be used in the preparation or professional development of DL teachers to work in educational establishments of various profiles. Key words: distance learning, distance learning teacher, distance education, models of distance learning.